COVID-19 PANDEMIC AND CHILD-PARENT RELATIONSHIP: A SERIAL MEDIATION MODEL BASED ON PARENTAL STRESS AND HARSH PARENTING (Proceeding of the International Conference on Arts and Humanities, 2024)
The purpose of this study is to relate the outbreak of COVID-19 to the child-parent relationship. Although the study uses a serial mediation model of parental stress and harsh parenting that makes this study innovative as compared to the other studies conducted in this area. Moreover, this study is also supplemented with the moderating role of the joint family system which is another unique element in the study. Hence the significance of this study has many folds as this study is not only for the increase of more research work on this burning issue but also aids in policy making avoid any further harm. In line with gaps highlighted by prior studies, this study collects data from parents from Pakistan in order to assess the impact of COVID-19 on child-parent relationships. Analysis has been made by applying SME through SMART-PLS which is effective to increase rigor and testability of the research. Findings indicated that COVID-19 resulted in a significant increase in parental stress that may also harm the child-parent relationship.
Keywords: Parental stress; Harsh Parenting; Pandemic; Child-Parent Relationship; COVID-19; Joint Family System